Modelling the roles of antibody titre and avidity in protection from Plasmodium falciparum malaria infection following RTS, S/AS01 vaccination. Issue 47 (3rd November 2020) - Thompson, Hayley A.; Hogan, Alexandra B.; Walker, Patrick G.T.; White, Michael T.; Cunnington, Aubrey J.; Ockenhouse, Christian F.; Ghani, Azra C.
Highlights: Models capturing key malaria life-cycle stages can help us evaluate vaccine candidates. Model fitting revealed antibody avidity to be an important determinant of RTS, S vaccine efficacy. High avidity and titre were associated with increased levels of vaccine efficacy. Did not identify any thresholds of protection for either immune marker. Abstract: Anti-circumsporozoite antibody titres have been established as an essential indicator for evaluating the immunogenicity and protective capacity of the RTS, S/AS01 malaria vaccine. However, a new delayed-fractional dose regime of the vaccine was recently shown to increase vaccine efficacy, from 62.5% (95% CI 29.4–80.1%) under the original dosing schedule to 86.7% (95% CI, 66.8–94.6%) without a corresponding increase in antibody titres. Here we reanalyse the antibody data from this challenge trial to determine whether IgG avidity may help to explain efficacy better than IgG titre alone by adapting a within-host mathematical model of sporozoite inoculation. We demonstrate that a model incorporating titre and avidity provides a substantially better fit to the data than titre alone. These results also suggest that in individuals with a high antibody titre response that also show high avidity (both metrics in the top tercile of observed values) delayed-fractional vaccination provided near perfect protection upon first challenge (98.2% [95% Credible Interval 91.6–99.7%]). This finding suggests that the quality of the vaccine induced antibody response is likely to be an important determinant in the development of highly efficacious pre-erythrocytic vaccines against malaria.